What issues need to be considered by nurses when faced with parents who refuse treatment for their children? A Critical Review - Donnison, Rachel (2008)
With increasing ethnic diversity in the United Kingdom, nurses will have to care for patients who have a different cultural background to themselves. Consent is required by parents for hospital treatment of children but there are occasions when particular interventions are refused because they contradict the family's religious or cultural beliefs. The aim of this dissertation is to conduct a critical review of the literature in relation to the nature of parental treatment refusal on the basis of religion or culture and to examine how nurses should approach such circumstances. A broad understanding of the way in which different health beliefs impact on parents' acceptance of western medicine is essential. Parental treatment refusals cause distress for healthcare professionals and family alike and so it is imperative that there is understanding and respect on both sides. Nurses experience role confusion as their duty to respect the beliefs of the family contradicts their need to protect the welfare of the child. Nurses have expressed feelings of anxiety and distress when looking after children from different cultures and therefore there is a need to improve nursing education. The power of medical authority to overrule parental treatment refusals has been questioned. Whilst treatment may be the best thing for the child in terms of their health, it may not be in terms of their complete well-being. There is a need for effective communication and negotiation between parents and healthcare professionals and the prevention of authoritative intervention is essential.